2021
DOI: 10.2147/imcrj.s321935
|View full text |Cite
|
Sign up to set email alerts
|

A Neonatal Hip Septic Arthritis Caused by Klebsiella pneumonia at Hawassa University Comprehensive Specialized Hospital Neonatal Unit, Hawassa, Sidama, Ethiopia

Abstract: Background: Neonatal hip septic arthritis is one of the rarest clinical conditions epidemiologically but with momentous long-term sequelae. Early detection and proper intervention have a paramount role in alleviating the shattering long-term effects. The clinical presentation of neonatal hip septic arthritis is very non-specific, with limited movement of the extremities and excessive crying during manipulations such as diaper changing. Our case was a 17-day-old male newborn who presented to our hospital after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…1 Neonatal hip septic arthritis presentation is very non-speci c, and is associated with poor prognosis, especially if the detection and intervention is delayed. 17 In our study those neonate who presented with hip joint involvement had unfavourable outcome then other joint involvement.…”
Section: Figure-2: Prognosis According To Mode Of Treatment (N=30)mentioning
confidence: 50%
“…1 Neonatal hip septic arthritis presentation is very non-speci c, and is associated with poor prognosis, especially if the detection and intervention is delayed. 17 In our study those neonate who presented with hip joint involvement had unfavourable outcome then other joint involvement.…”
Section: Figure-2: Prognosis According To Mode Of Treatment (N=30)mentioning
confidence: 50%
“…However, several studies have also shown good results without surgery in children with septic arthritis. (16)(17)(18)(19). The same study concluded that surgery is complementary to antibiotics in the management of arthritis and not complementary resource antibiotics, postulating that the joint must be washed and the pus has to be drained.…”
Section: Discussionmentioning
confidence: 96%